The branding of tourist destinations : theoretical and empirical insights - Camilleri, Mark Anthony, 1976- (Emerald Publishing Limited, 2018)
The marketing of tourist destinations requires continuous strategic planning and decision making. 'The Branding of Tourist Destinations:Theoretical and Empirical Insights 'provides researchers and practitioners with an in-depth understanding of different tourism products, marketing strategies and destination branding tactics, as well as useful insights into sustainable and responsible tourism practices. The authors present contemporary conceptual discussions and empirical studies on several aspects of destination branding that help contextualise the attractiveness of a range of tourist destinations. In particular, they explore how tourism marketers, including destination management organisations (DMOs), formulate strategies and tactics to attract prospective visitors. This book also sheds light on the latest industry developments in travel, tourism, hospitality and events indifferent contexts around the world, including destinations in Sweden, Portugal, Spain, Italy and Ecuador.
Prelims -- Chapter 1: The marketing environment of tourist destinations -- Chapter 2: Branding places and tourist destinations: a conceptualisation and review -- Chapter 3: A stakeholder approach for destination management organisations -- Chapter 4: The destination branding through multisensory experiences: case studies from Sweden -- Chapter 5: The development of the agritourism sector in Campania, Italy -- Chapter 6: Using the destination's heritage, language, lifestyle and 'made in Italy' as a tourism development model -- Chapter 7: The consumer-based brand equity of music events: two case studies from Portugal -- Chapter 8: Branding Porto: a case study of the 'essence of wine' -- Chapter 9: Oleotourism development in Jaén, Spain -- Chapter 10: The hotel managers' attitudes towards environmental responsibility. an empirical study from Ecuador -- Chapter 11: The moderating effect of perceived value on the relationship between country image and destination brand extension -- Chapter 12: Exploring customers' attitudes towards the hospitality brands in India: a social identity perspective Index.
Includes index.
Print version record
Keywords: Tourism -- Marketing; Branding (Marketing); Business & Economics -- Industries -- Hospitality, Travel & Tourism; Tourism industry